Who Protects Clinical Learners in Canada? Ethical Considerations for Institutional Policy on Patient Bias - Drews, Sun; Barned, Claudia (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
Navigating the social dynamics of clinical spaces can be an added challenge to the complexities of clinical work. Acts of bias and discrimination from patients have been found to affect healthcare workers both physically and psychologically. As more attention is paid to addressing discrimination by patients, we raise attention to the experiences and unique needs of clinical learners. Given that learners play a vital role in the functioning of hospital ecosystems, we advocate for the inclusion of their voices in any revision to policy and practice. In this paper, we critically examine the academic literature on learner’s experiences with mistreatment from patients, and their families. We outline the major gaps in policy, process, training, and institutional culture, noting the urgent need for institutions to address these gaps in ways that are meaningful to learners. Our goal is to highlight the lack of bioethics attention to this matter and propose areas where we can add value and support. With this goal in mind, we present a series of tables with guiding values, ethical considerations and questions for institutions.